Double cocktail immunostains with high molecular weight cytokeratin and GATA-3: useful stain to discriminate in situ involvement of prostatic ducts or acini from stromal invasion by urothelial carcinoma in the prostate - Junghye Lee; Youngeun Yoo; Sanghui Park; Min-Sun Cho; Sun Hee Sung; Jae Y. Ro (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background Distinguishing prostatic stromal invasion (PSI) by urothelial carcinoma (UC) from in situ UC involving prostatic ducts or acini with no stromal invasion (in situ involvement) may be challenging on hematoxylin and eosin stained sections. However, the distinction between them is important because cases with PSI show worse prognosis. This study was performed to assess the utility of double cocktail immunostains with high molecular weight cytokeratin (HMWCK) and GATA-3 to discriminate PSI by UC from in situ UC involvement of prostatic ducts or acini in the prostate. Methods Among 117 radical cystoprostatectomy specimens for bladder UCs, 25 cases showed secondary involvement of bladder UC in prostatic ducts/acini only or associated stromal invasion and of these 25 cases, seven cases revealed equivocal PSI. In these seven cases with equivocal PSI, HMWCK, and GATA-3 double immunohistochemical stains were performed to identify whether this cocktail stain is useful to identify the stromal invasion. Results In all cases, basal cells of prostate glands showed strong cytoplasmic staining for HMWCK and UC cells showed strong nuclear staining for GATA-3. In cases with stromal invasion of UC, GATA-3-positive tumor cells in the prostatic stroma without surrounding HMWCK-positive basal cells were highlighted and easily recognized. Among seven equivocal cases, two cases showed PSI and five in situ UC in the prostate. In two cases, the original diagnoses were revised. Conclusions Our study suggested that HMWCK and GATA-3 double stains could be utilized as an adjunct method in the distinction between PSI by UC from in situ UC involving prostatic ducts or acini.